Effectiveness Of The Use Of Instagram Social Media On Personal Branding Joko Widodo In The First Voters 2019 Election - Ahnaf Rifky Saputra (Jurusan Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2019)
In this digital era, all activities can be published to the public through social media. Many groups of people actively use social media ranging from students, adults, entrepreneurs and state officials. One of them is the seventh President of the Republic of Indonesia, Ir. H. Joko Widodo. Joko Widodo has a variety of social media platforms, social media with the most followers among other social media is Instagram. With a total of 16.5 million followers making him the leader of the country with the second most followers in the world. The content of uploads on Instagram of Joko Widodo is diverse and very massive, the things Joko Widodo does on Instagram social media is one way to form personal branding. Personal branding is a unique phenomenon because basically all people have their own characteristics, to get the results of long-lasting branding and provide maximum benefits, the branding process must come from authentic, real and original evidence. This study aims to determine how effective the use of social media instagram is for the formation of Joko Widodo's personal Branding to the 2019 First Election Voters who are still confused and need references to make choices in using their voting rights. This study uses a descriptive quantitative method of two variables. The independent variable in this study is the effectiveness of using social media instagram while the dependent variable is Joko Widodo's personal branding. This research was conducted by distributing questionnaires to 100 respondents using the Nonprobality Sampling technique. The results of this study state that the use of Instagram social media in delivering the desired message falls into the effective category with a percentage of 74.9% while the formation of personal branding for the first voters is included in the effective category with a percentage of 81.1%. The conclusion of this study is that the communication carried out by Joko Widodo's Instagram social media account took place effectively and had a positive effect on the formation of Joko Widodo's personal branding for the first voters of the 2019 Election. Keywords: Social Media, Instagram, Personal Branding, First Voters